Development of Application Based on Augmented Reality to Improve Student's Spatial Ability - Muslih Hasan Pambudi; Amin Suyitno; Zaenuri Mastur (Universitas Syiah Kuala, 2022)
Technology has become a crucial part of the learning process and a facilitator of the interaction between students and teachers. Spatial ability is a crucial ability in mathematics learning and success in STEM. In this case, Augmented Reality (AR) in mathematics learning can facilitate the abstraction of mathematics that represents a new representation of mathematics concept. The objectives of this studywere to develop an application using AR which was further used to improve the spatial ability of Junior High School students.Meanwhile, the method used in this study was RD using the ADDIE model and quantitative approach through t-test. In this case, 64 students of 8thgrade in Junior High School were involved as the research samples, where 32 students were in the control class and 32 students were in the experimental class. The results of this study were that the AR application was feasible to use in mathematics learning and its application enabled teacher and students to learn solid geometry using Augmented Reality with the object that can be manipulated, interact in real-time, and measure objects in the real world. It was also obtained that the learning outcomes of students who used the application were higher than the learning outcomes of students who did not use application, indicating that the application could increase stdudents spatial ability.